THE EFFECT OF PROFIT SHARING FINANCING AND QARDH FINANCING ON NET PROFIT SHARIA BANK IN INDONESIA - Maulana, Dede Rapsanjani; Ruchjana, Eva Theresna; Nurdiansyah, Dian Hakip (El Dinar: Jurnal Keuangan dan Perbankan Syariah, 2020)
This study aims to examine the effect of Profit Sharing Financing and Qardh Financing on Net Profit Sharia Commercial Bank. The method used is descriptive statistics with quantitative approach that is through the classical assumption test to analyze the data and multiple linear regression analysis to determine the level of relations or effect that given by Profit Sharing Financing and Qardh Financing on Net Profit and processed by using software SPSS 16. While data used are secondary data with quantitative data types during the period 2014- 2019. Population of this study is Sharia Commercial Bank companies with sampling method that is purposive sampling, so that the number of observations obtained as many as 6 companies. Based on the result of the research, the test of simultaneously results with the statistical test show that the variable Profit Sharing Financing and Qardh Financing simultaneously affected. The result of coefficient determination shows that Net Profit (Y) is influenced by Profit Sharing Financing (X1), Qardh Financing (X2) as much as 64.1% and the remaining left is influenced by other variables as much as 35.9%.